Vidiki dualizma znotraj zdravstvene službe - Klančnik-Gruden, Maja (Obzornik zdravstvene nege, 2000)
The relations inside health care system are marked by different oppositions. The basic dualism, the opposition between man and woman, respectively doctor and nurse derives from the society as a whole. The article proceeds from anthropological description of primary dualistic organizations and projects the basic idea of dualism on health service. The first part of the article analyses workforce in the National Health Care Service in Great Britain and compares it with the workforce in the Public Health Care Service in the Republic of Slovenia. In conclusion the impact of dualistic aspects of health services on the quality of health care of clients is presented.
Keywords: Great britain; Health manpower; Health services; Nursing care; organizacija; organization; Organization and administration; Physician-nurse relations; Public health; Slovenia; Slovenija; zdravstvene službe